2021
DOI: 10.1097/med.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and metabolic consequences in patients with asymptomatic adrenal adenomas

Abstract: Purpose of review The incidence of adrenal tumors has increased over the past 20 years, most of which are incidentally discovered nonfunctioning adenomas (NFA) and tumors with mild autonomous cortisol secretion (MACS). This review aimed to summarize recent progress in understanding cardiometabolic risk in patients with NFA and MACS and to provide updates on the effect of treatment on improving outcomes in this population. Recent findings NFA and MACS ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…[24][25][26][27][28] Over the last few years, new discoveries have emerged regarding the deleterious effects of ACS, such as an increased risk of periodontitis, 29 mental disorders, and worsening of quality of life. 30 Although with less evidence than in ACS, but increasing, a greater cardio-metabolic risk has been found in patients with apparently NFAIs than in the general population [10][11][12]14,[31][32][33][34][35] (Figure 1 and Table 1). In fact, in a recent study, 36 it has been observed that the cardio-metabolic risk of patients with ACS and NFAI was higher than in the general population, but did not differ between the two groups when a stratification by body mass index (BMI) was performed, which suggests that both entities are equally deleterious for the cardiometabolic system.…”
Section: Cardiometabolic Implications Of Nfaismentioning
confidence: 99%
“…[24][25][26][27][28] Over the last few years, new discoveries have emerged regarding the deleterious effects of ACS, such as an increased risk of periodontitis, 29 mental disorders, and worsening of quality of life. 30 Although with less evidence than in ACS, but increasing, a greater cardio-metabolic risk has been found in patients with apparently NFAIs than in the general population [10][11][12]14,[31][32][33][34][35] (Figure 1 and Table 1). In fact, in a recent study, 36 it has been observed that the cardio-metabolic risk of patients with ACS and NFAI was higher than in the general population, but did not differ between the two groups when a stratification by body mass index (BMI) was performed, which suggests that both entities are equally deleterious for the cardiometabolic system.…”
Section: Cardiometabolic Implications Of Nfaismentioning
confidence: 99%